Analysis of SARS-CoV-2 Spike Protein Variants with Recombinant Reporter Viruses Created from a Bacmid System - Cordsmeier, Arne; Jungnickl, Doris; Herrmann, Alexandra; Korn, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2023)
SARS-CoV-2, the causative agent of COVID-19, has spread around the world with more than 700 million cases and 6.8 million deaths. Various variants of concern (VoC) have emerged due to mutations and recombination and concurrent selection for increased viral fitness and immune evasion. The viral protein that primarily determines the pathogenicity, infectivity, and transmissibility is the Spike protein. To analyze the specific impact of variant Spike proteins on infection dynamics, we constructed SARS-CoV-2 with a uniform B.1 backbone but with alternative Spike proteins. In addition, ORF6 was replaced by EYFP as a biological safety measure, and for use of this well-established reporter. We show that namely the delta variant Spike proteins cause a distinct phenotype from the wild type (B.1, D614G) and other variants of concern. Furthermore, we demonstrate that the omicron BA.1 Spike results in lower viral loads and a less efficient spread in vitro. Finally, we utilized viruses with the two different reporters EYFP and mCherry to establish a competitive growth assay, demonstrating that most but not all Spike variant viruses were able to outcompete wild type SARS-CoV-2 B.1.
CRIS-Team Scopus Importer:2023-05-26
Keywords: SARS-CoV-2; Spike protein; variants of concern

Attenuation of SARS-CoV-2 replication and associated inflammation by concomitant targeting of viral and host cap 2'-O-ribose methyltransferases - Bergant, Valter; Yamada, Shintaro; Grass, Vincent; Tsukamoto, Yuta; Lavacca, Teresa; Krey, Karsten; Muhlhofer, Maria-Teresa; Wittmann, Sabine; Enßer, Armin; Herrmann, Alexandra; Vom Hemdt, Anja; Tomita, Yuriko; et al. (EMBO Journal, 2022)
The SARS-CoV-2 infection cycle is a multistage process that relies on functional interactions between the host and the pathogen. Here, we repurposed antiviral drugs against both viral and host enzymes to pharmaceutically block methylation of the viral RNA 2'-O-ribose cap needed for viral immune escape. We find that the host cap 2'-O-ribose methyltransferase MTr1 can compensate for loss of viral NSP16 methyltransferase in facilitating virus replication. Concomitant inhibition of MTr1 and NSP16 efficiently suppresses SARS-CoV-2 replication. Using in silico target-based drug screening, we identify a bispecific MTr1/NSP16 inhibitor with anti-SARS-CoV-2 activity in vitro and in vivo but with unfavorable side effects. We further show antiviral activity of inhibitors that target independent stages of the host SAM cycle providing the methyltransferase co-substrate. In particular, the adenosylhomocysteinase (AHCY) inhibitor DZNep is antiviral in in vitro, in ex vivo, and in a mouse infection model and synergizes with existing COVID-19 treatments. Moreover, DZNep exhibits a strong immunomodulatory effect curbing infection-induced hyperinflammation and reduces lung fibrosis markers ex vivo. Thus, multispecific and metabolic MTase inhibitors constitute yet unexplored treatment options against COVID-19.
CRIS-Team WoS Importer:2022-08-05

A viral kinase counteracts in vivo restriction of murine cytomegalovirus by SAMHD1 - Deutschmann, Janina; Schneider, Andrea; Gruska, Iris; Vetter, Barbara; Thomas, Dominique; Kießling, Melissa; Wittmann, Sabine; Herrmann, Alexandra; Schindler, Michael; Milbradt, Jens; Ferreirós, Nerea; Winkler, Thomas; et al. (Nature Microbiology, 2019)
The deoxynucleotide triphosphate (dNTP) hydrolase SAMHD1 inhibits retroviruses in non-dividing myeloid cells. Although antiviral activity towards DNA viruses has also been demonstrated, the role of SAMHD1 during cytomegalovirus (CMV) infection remains unclear. To determine the impact of SAMHD1 on the replication of CMV, we used murine CMV (MCMV) to infect a previously established SAMHD1 knockout mouse model and found that SAMHD1 inhibits the replication of MCMV in vivo. By comparing the replication of MCMV in vitro in myeloid cells and fibroblasts from SAMHD1-knockout and control mice, we found that the viral kinase M97 counteracts SAMHD1 after infection by phosphorylating the regulatory residue threonine 603. The phosphorylation of SAMHD1 in infected cells correlated with a reduced level of dNTP hydrolase activity and the loss of viral restriction. Together, we demonstrate that SAMHD1 acts as a restriction factor in vivo and we identify the M97-mediated phosphorylation of SAMHD1 as a previously undescribed viral countermeasure.
CRIS-Team Scopus Importer:2019-11-01

Cloning of a passage-free SARS-CoV-2 genome and mutagenesis using red recombination - Herrmann, Alexandra; Jungnickl, Doris; Cordsmeier, Arne; Peter, Antonia Sophia; Überla, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2021)
The ongoing pandemic coronavirus (CoV) disease 2019 (COVID-19) by severe acute respiratory syndrome CoV-2 (SARS-CoV-2) has already caused substantial morbidity, mortality, and economic devastation. Reverse genetic approaches to generate recombinant viruses are a powerful tool to characterize and understand newly emerging viruses. To contribute to the global efforts for countermeasures to control the spread of SARS-CoV-2, we developed a passage-free SARS-CoV-2 clone based on a bacterial artificial chromosome (BAC). Moreover, using a Lambda-based Red recombination, we successfully generated different reporter and marker viruses, which replicated similar to a clinical isolate in a cell culture. Moreover, we designed a full-length reporter virus encoding an additional artificial open reading frame with wild-type-like replication features. The virus-encoded reporters were successfully applied to ease antiviral testing in cell culture models. Furthermore, we designed a new marker virus encoding 3xFLAG-tagged nucleocapsid that allows the detection of incoming viral particles and, in combination with bio-orthogonal labeling for the visualization of viral RNA synthesis via click chemistry, the spatiotemporal tracking of viral replication on the single-cell level. In summary, by applying BAC-based Red recombination, we developed a powerful, reliable, and convenient platform that will facilitate studies answering numerous questions concerning the biology of SARS-CoV-2.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Bacterial artificial chromosome; COVID-19 pandemic; Incoming viral particles; Recombinant virus; Red recombination; Reporter virus; Reverse genetics; SARS-CoV-2

Iota-Carrageenan Inhibits Replication of the SARS-CoV-2 Variants of Concern Omicron BA.1, BA.2 and BA.5 - Setz, Christian; Große, Maximilian; Fröba, Maria; Auth, Janina; Rauch, Pia; Herrmann, Alexandra; Cordsmeier, Arne; Enßer, Armin; Schindler, Michael; Morokutti-Kurz, Martina; Graf, Philipp; Engel, Benedikt; et al. (Nutraceuticals, 2023)
Even with its endemic transition, the COVID-19 pandemic remains a public health threat, particularly in the light of emerging variants of concern (VoCs) and the need for pandemic preparedness in the future. In November 2021, the SARS-CoV-2 VoC Omicron emerged and its subvariants BA.1, BA.2 and BA.5 became predominant. Although the protease inhibitor Paxlovid® and the polymerase inhibitors Molnupiravir and Remdesivir were approved as specific antiviral treatment options for COVID-19 patients in the early stages after infection, effective prophylactically acting substances without adverse effects are not available yet. In a recent study, we demonstrated that iota-carrageenan, a sulfated polysaccharide extracted from red seaweed, efficiently inhibits the replication of the SARS-CoV-2 Wuhan Type and the VoCs Alpha, Beta, Gamma and Delta. Now, we extended this study by investigating the antiviral effects of iota-, lambda- and kappa-carrageenans on the VoC Omicron subvariants BA.1, BA.2 and BA.5. Using a VoC Omicron BA.1 spike pseudotyped murine leukemia virus (BA.1 MLVOMVLP) as well as patient-derived SARS-CoV-2 Omicron isolates BA.1, BA.2 and BA.5 (SARS-CoV-2OM BA.1, SARS-CoV-2OM BA.2 and SARS-CoV-2OM BA.5), we demonstrate that iota-carrageenan exhibits similar antiviral activity against all analyzed Omicron subvariants. As with other VoCs shown before, the biologically inert iota-carrageenan was more efficient than kappa- and lambda-carrageenan. Altogether, these results confirm that, independent of the current and potential future variants, the physical barrier provided by iota-carrageenan might be applicable for prophylaxis and early treatment of SARS-CoV-2 infections.
CRIS-Team Scopus Importer:2025-07-10
Keywords: BA.1; BA.2; BA.5; carrageenan types; coronavirus; COVID-19; iota-carrageenan; kappa-carrageenan; lambda-carrageenan; omicron; omicron subvariants; pseudotyping; SARS-CoV-2; sulfated polymer; variant of concern; variants of concern; virus variants

Methodological development of a multi-readout assay for the assessment of antiviral drugs against sars-cov-2 - Hahn, Friedrich; Häge, Sigrun; Herrmann, Alexandra; Wangen, Christina; Kicuntod, Jintawee; Jungnickl, Doris; Tillmanns, Julia; Müller, Regina; Fraedrich, Kirsten; Überla, Klaus; Kohlhof, Hella; Enßer, Armin; et al. (Pathogens, 2021)
Currently, human infections with the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) are accelerating the ongoing spread of the pandemic. Several innovative types of vaccines have already been developed, whereas effective options of antiviral treatments still await a scientific implementation. The development of novel anti-SARS-CoV-2 drug candidates demands skillful strategies and analysis systems. Promising results have been achieved with first generation direct-acting antivirals targeting the viral polymerase RdRp or the protease 3CLpro . Such recently approved or investigational drugs like remdesivir and GC376 represent a basis for further development and optimization. Here, we establish a multi-readout assay (MRA) system that enables the antiviral assessment and mechanistic characterization of novel test compounds, drug repurposing and combination treatments. Our SARS-CoV-2-specific MRA combines the quantitative measurement of several parameters of virus infection, such as the intracellular production of proteins and genomes, enzymatic activities and virion release, as well as the use of reporter systems. In this regard, the antiviral efficacy of remdesivir and GC376 has been investigated in human Caco-2 cells. The readouts included the use of spike-and double-strand RNA-specific monoclonal antibodies for in-cell fluorescence imaging, a newly generated recombinant SARS-CoV-2 reporter virus d6YFP, the novel 3CLpro-based FRET CFP::YFP and the previously reported FlipGFP reporter assays, as well as viral genome-specific RT-qPCR. The data produced by our MRA confirm the high antiviral potency of these two drugs in vitro. Combined, this MRA approach may be applied for broader analyses of SARS-CoV-2-specific antivirals, including compound screenings and the characterization of selected drug candidates.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anti-coronaviral treatment; Antiviral drug assessment; Candidate drugs; COVID-19 pandemic; Cultured human cells; Methodological development; Multi-readout assay (MRA); SARS-CoV-2 infection

Nsp16 shields SARS–CoV-2 from efficient MDA5 sensing and IFIT1-mediated restriction - Ruß, Alina; Wittmann, Sabine; Tsukamoto, Yuta; Herrmann, Alexandra; Deutschmann, Janina; Lagisquet, Justine; Enßer, Armin; Kato, Hiroki; Gramberg, Thomas (EMBO Reports, 2022)
Methylation of the mRNA 5′ cap by cellular methyltransferases enables efficient translation and avoids recognition by innate immune factors. Coronaviruses encode viral 2′-O-methyltransferases to shield their RNA from host factors. Here, we generate recombinant SARS–CoV-2 harboring a catalytically inactive 2′-O-methyltransferase Nsp16, Nsp16mut, and analyze viral replication in human lung epithelial cells. Although replication is only slightly attenuated, we find SARS–CoV-2 Nsp16mut to be highly immunogenic, resulting in a strongly enhanced release of type I interferon upon infection. The elevated immunogenicity of Nsp16mut is absent in cells lacking the RNA sensor MDA5. In addition, we report that Nsp16mut is highly sensitive to type I IFN treatment and demonstrate that this strong antiviral effect of type I IFN is mediated by the restriction factor IFIT1. Together, we describe a dual role for the 2′-O-methyltransferase Nsp16 during SARS–CoV-2 replication in avoiding efficient recognition by MDA5 and in shielding its RNA from interferon-induced antiviral responses, thereby identifying Nsp16 as a promising target for generating attenuated and highly immunogenic SARS–CoV-2 strains and as a potential candidate for therapeutic intervention.
CRIS-Team Scopus Importer:2022-11-04
Keywords: 2′-O-methyltransferase; IFIT1; MDA5; Nsp16; SARS–CoV-2

ORF3c is expressed in SARS-CoV-2-infected cells and inhibits innate sensing by targeting MAVS - Müller, Martin; Herrmann, Alexandra; Fujita, Shigeru; Uriu, Keiya; Kruth, Carolin; Strange, Adam; Kolberg, Jan E.; Schneider, Markus; Ito, Jumpei; Müller, Marcel A.; Drosten, Christian; Enßer, Armin; et al. (EMBO Reports, 2023)
Most SARS-CoV-2 proteins are translated from subgenomic RNAs (sgRNAs). While the majority of these sgRNAs are monocistronic, some viral mRNAs encode more than one protein. One example is the ORF3a sgRNA that also encodes ORF3c, an enigmatic 41-amino-acid peptide. Here, we show that ORF3c is expressed in SARS-CoV-2-infected cells and suppresses RIG-I- and MDA5-mediated IFN-β induction. ORF3c interacts with the signaling adaptor MAVS, induces its C-terminal cleavage, and inhibits the interaction of RIG-I with MAVS. The immunosuppressive activity of ORF3c is conserved among members of the subgenus sarbecovirus, including SARS-CoV and coronaviruses isolated from bats. Notably, however, the SARS-CoV-2 delta and kappa variants harbor premature stop codons in ORF3c, demonstrating that this reading frame is not essential for efficient viral replication in vivo and is likely compensated by other viral proteins. In agreement with this, disruption of ORF3c does not significantly affect SARS-CoV-2 replication in CaCo-2, CaLu-3, or Rhinolophus alcyone cells. In summary, we here identify ORF3c as an immune evasion factor of SARS-CoV-2 that suppresses innate sensing in infected cells.
CRIS-Team Scopus Importer:2023-11-03
Keywords: cryptic open reading frames; IFN antagonist; immune evasion; ORF3c; SARS-CoV-2

SAMHD1 in Retroviral Restriction and Innate Immune Sensing–Should We Leash the Hound? - Herrmann, Alexandra; Happel, Anna-Ursula; Gramberg, Thomas (Current HIV Research, 2016)
The antiviral restriction factor SAM domain and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase and thereby contributes to the regulation of intracellular dNTP levels. SAMHD1 blocks retroviral infection at the level of reverse transcription in myeloid cells and resting CD4+ T cells and is counteracted by the accessory protein Vpx, which is encoded by human immunodeficiency virus 2 (HIV-2) and several simian immunodeficiency virus (SIV) strains. Recently, it has been shown that the antiviral activity of SAMHD1 in myeloid dendritic cells (DC) hampers the induction of an efficient immune response directed against HIV-1.Within this review, we will summarize recent advances on the biology of SAMHD1 and its function as an antiviral restriction factor. In addition, we will discuss its role in autoimmunity and the antiviral immune response directed against HIV-1 and will evaluate the possibility of modulating SAMHD1 activity to generate an enhanced antiretroviral immune response.
EVALuna2:8304

SMYD2 Inhibition Downregulates TMPRSS2 and Decreases SARS-CoV-2 Infection in Human Intestinal and Airway Epithelial Cells - Yu, Yidong; Herrmann, Alexandra; Thonn, Veronika; Cordsmeier, Arne; Neurath, Markus; Enßer, Armin; Becker, Christoph (Cells, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 has lasted for more than two years. Despite the presence of very effective vaccines, the number of virus variants that escape neutralizing antibodies is growing. Thus, there is still a need for effective antiviral treatments that target virus replication independently of the circulating variant. Here, we show for the first time that deficiency or pharmacological inhibition of the cellular lysine-methyltransferase SMYD2 decreases TMPRSS2 expression on both mRNA and protein levels. SARS-CoV-2 uses TMPRSS2 for priming its spike protein to infect target cells. Treatment of cultured cells with the SMYD2 inhibitors AZ505 or BAY598 significantly inhibited viral replication. In contrast, treatment of Vero E6 cells, which do not express detectable amounts of TMPRSS2, had no effect on SARS-CoV-2 infection. Moreover, by generating a recombinant reporter virus that expresses the spike protein of the Delta variant of SARS-CoV-2, we demonstrate that BAY598 exhibits similar antiviral activity against this variant of concern. In summary, SMYD2 inhibition downregulates TMPRSS2 and blocks viral replication. Targeting cellular SMYD2 represents a promising tool to curtail SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2022-04-29
Keywords: antiviral treatment; AZ505; BAY598; COVID-19; SARS-CoV-2; SMYD2; TMPRSS2

Spike and nsp6 are key determinants of SARS-CoV-2 Omicron BA.1 attenuation - Chen, Da Yuan; Chin, Chue Vin; Kenney, Devin; Tavares, Alexander H.; Khan, Nazimuddin; Conway, Hasahn L.; Liu, Guan Qun; Choudhary, Manish C.; Gertje, Hans P.; O’Connell, Aoife K.; Adams, Scott; Kotton, Darrell N.; et al. (Nature, 2023)
The SARS-CoV-2 Omicron variant is more immune evasive and less virulent than other major viral variants that have so far been recognized1–12. The Omicron spike (S) protein, which has an unusually large number of mutations, is considered to be the main driver of these phenotypes. Here we generated chimeric recombinant SARS-CoV-2 encoding the S gene of Omicron (BA.1 lineage) in the backbone of an ancestral SARS-CoV-2 isolate, and compared this virus with the naturally circulating Omicron variant. The Omicron S-bearing virus robustly escaped vaccine-induced humoral immunity, mainly owing to mutations in the receptor-binding motif; however, unlike naturally occurring Omicron, it efficiently replicated in cell lines and primary-like distal lung cells. Similarly, in K18-hACE2 mice, although virus bearing Omicron S caused less severe disease than the ancestral virus, its virulence was not attenuated to the level of Omicron. Further investigation showed that mutating non-structural protein 6 (nsp6) in addition to the S protein was sufficient to recapitulate the attenuated phenotype of Omicron. This indicates that although the vaccine escape of Omicron is driven by mutations in S, the pathogenicity of Omicron is determined by mutations both in and outside of the S protein.
CRIS-Team Scopus Importer:2023-02-24

Spike residue 403 affects binding of coronavirus spikes to human ACE2 - Zech, Fabian; Schniertshauer, Daniel; Jung, Christoph; Herrmann, Alexandra; Cordsmeier, Arne; Xie, Qinya; Nchioua, Rayhane; Bozzo, Caterina Prelli; Volcic, Meta; Koepke, Lennart; Mueller, Janis A.; Krueger, Jana; et al. (Nature Communications, 2021)
The bat sarbecovirus RaTG13 is a close relative of SARS-CoV-2, the cause of the COVID-19 pandemic. However, this bat virus was most likely unable to directly infect humans since its Spike (S) protein does not interact efficiently with the human ACE2 receptor. Here, we show that a single T403R mutation increases binding of RaTG13 S to human ACE2 and allows VSV pseudoparticle infection of human lung cells and intestinal organoids. Conversely, mutation of R403T in the SARS-CoV-2 S reduces pseudoparticle infection and viral replication. The T403R RaTG13 S is neutralized by sera from individuals vaccinated against COVID-19 indicating that vaccination might protect against future zoonoses. Our data suggest that a positively charged amino acid at position 403 in the S protein is critical for efficient utilization of human ACE2 by S proteins of bat coronaviruses. This finding could help to better predict the zoonotic potential of animal coronaviruses.
CRIS-Team Scopus Importer:2021-12-10

The SAMHD1-mediated block of LINE-1 retroelements is regulated by phosphorylation - Herrmann, Alexandra; Wittmann, Sabine; Thomas, Dominique; Shepard, Caitlin N.; Kim, Baek; Ferreiros, Nerea; Gramberg, Thomas (Mobile DNA, 2018)
Background: The restriction factor SAMHD1 regulates intracellular nucleotide level by degrading dNTPs and blocks the replication of retroviruses and DNA viruses in non-cycling cells, like macrophages or dendritic cells. In patients, inactivating mutations in samhd1 are associated with the autoimmune disease Aicardi-Goutieres Syndrome (AGS). The accumulation of intracellular nucleic acids derived from endogenous retroelements thriving in the absence of SAMHD1 has been discussed as potential trigger of the autoimmune reaction. In vitro, SAMHD1 has been found to restrict endogenous retroelements, like LINE-1 elements (L1). The mechanism, however, by which SAMHD1 blocks endogenous retroelements, is still unclear. Results: Here, we show that SAMHD1 inhibits the replication of L1 and other endogenous retroelements in cycling cells. By applying GFP- and neomycin-based reporter assays we found that the anti-L1 activity of SAMHD1 is regulated by phosphorylation at threonine 592 (T592). Similar to the block of HIV, the cofactor binding site and the enzymatic active HD domain of SAMHD1 proofed to be essential for restriction of L1 elements. However, phosphorylation at T592 did not correlate with the dNTP hydrolase activity of SAMHD1 in cycling 293T cells suggesting an alternative mechanism of regulation. Interestingly, we found that SAMHD1 binds to ORF2 protein of L1 and that this interaction is regulated by T592 phosphorylation. Together with the finding that the block is also active in cycling cells, our results suggest that the SAMHD1-mediated inhibition of L1 is similar but not identical to HIV restriction. Conclusion: Our findings show conclusively that SAMHD1 restricts the replication of endogenous retroelements in vitro. The results suggest that SAMHD1 is important for maintaining genome integrity and support the idea of an enhanced replication of endogenous retroelements in the absence of SAMHD1 in vivo, potentially triggering autoimmune diseases like AGS. Our analysis also contributes to the better understanding of the activities of SAMHD1 in antiviral defense and nucleotide metabolism. The finding that the phosphorylation of SAMHD1 at T592 regulates its activity against retroelements but not necessarily intracellular dNTP level suggests that the dNTP hydrolase activity might not be the only function of SAMHD1 important for its antiviral activity and for controlling autoimmunity.
EVALuna2:35283

The Trimeric Artesunate Analog TF27, a Broadly Acting Anti-Infective Model Drug, Exerts Pronounced Anti-SARS-CoV-2 Activity Spanning Variants and Host Cell Types - Hahn, Friedrich; Wangen, Christina; Häge, Sigrun; Herrmann, Lars; Herrmann, Alexandra; Tsogoeva, Svetlana; Marschall, Manfred (Pharmaceutics, 2023)
Starting in 2019, the spread of respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated pandemic of the corona virus disease (COVID-19) has led to enormous efforts in the development of medical countermeasures. Although innovative vaccines have scaled back the number of severe COVID cases, the emergence of the omicron variant (B.1.1.529) illustrates how vaccine development struggles to keep pace with viral evolution. On the other hand, while the recently approved antiviral drugs remdesivir, molnupiravir, and Paxlovid are considered as broadly acting anti-coronavirus therapeutics, only molnupiravir and Paxlovid are orally available and none of these drugs are recommended for prophylactic use. Thus, so far unexploited small molecules, targeting strategies, and antiviral mechanisms are urgently needed to address issues in the current pandemic and in putative future outbreaks of newly emerging variants of concern. Recently, we and others have described the anti-infective potential and particularly the pronounced antiviral activity of artesunate and related compounds of the trioxane/sesquiterpene class. In particular, the trimeric derivative TF27 demonstrated strong anti-cytomegalovirus activity at nanomolar concentrations in vitro as well as in vivo efficacy after oral administration in therapeutic and even prophylactic treatment settings. Here, we extended this analysis by evaluating TF27 for its anti-SARS-CoV-2 potential. Our main findings are as follows: (i) compound TF27 exerted strong anti-SARS-CoV-2 activity in vitro (EC50 = 0.46 ± 0.20 µM), (ii) antiviral activity was clearly distinct from the induction of cytotoxicity, (iii) pretreatment with TF27 prevented virus replication in cultured cells, (iv) antiviral activity has likewise been demonstrated in Calu-3 human lung and Caco-2 human colon cells infected with wild-type, delta, or omicron SARS-CoV-2, respectively, and (v) analysis of TF27 combination treatments has revealed synergistic interaction with GC376, but antagonistic interaction with EIDD-1931. Combined, the data demonstrated the pronounced anti-SARS-CoV-2 activity of TF27 and thus highlight the potential of trioxane compounds for further pharmacologic development towards improved options for COVID-specific medication.
CRIS-Team Scopus Importer:2023-02-03
Keywords: artesunate and analogs; broad-spectrum inhibitory properties; host-directed drug targeting; pronounced anti-SARS-CoV-2 activity; SARS-CoV-2 infection; trimeric analog TF27

TRIM19/PML Restricts HIV Infection in a Cell Type-Dependent Manner - Kahle, Tanja; Volkmann, Bianca; Eißmann, Kristin; Herrmann, Alexandra; Schmitt, Sven; Wittmann, Sabine; Merkel, Laura; Reuter, Nina; Stamminger, Thomas; Gramberg, Thomas (Viruses, 2016)
The promyelocytic leukemia protein (PML) is the main structural component of the nuclear matrix structures termed nuclear domain 10 (ND10) or PML nuclear bodies (PML-NBs). PML and ND10 structures have been shown to mediate an intrinsic immune response against a variety of different viruses. Their role during retroviral replication, however, is still controversially discussed. In this study, we analyzed the role of PML and the ND10 components Daxx and Sp100 during retroviral replication in different cell types. Using cell lines exhibiting a shRNA-mediated knockdown, we found that PML, but not Daxx or Sp100, inhibits HIV and other retroviruses in a cell type-dependent manner. The PML-mediated block to retroviral infection was active in primary human fibroblasts and murine embryonic fibroblasts but absent from T cells and myeloid cell lines. Quantitative PCR analysis of HIV cDNA in infected cells revealed that PML restricts infection at the level of reverse transcription. Our findings shed light on the controversial role of PML during retroviral infection and show that PML contributes to the intrinsic restriction of retroviral infections in a cell type-dependent manner.
EVALuna2:8305

Validation of nuclear receptor RORγ isoform 1 as a novel host-directed antiviral target based on the modulation of cholesterol levels - Wangen, Christina; Raithel, Andrea; Tillmanns, Julia; Gege, Christian; Herrmann, Alexandra; Vitt, Daniel; Kohlhof, Hella; Marschall, Manfred; Hahn, Friedrich (Antiviral Research, 2024)
Currently, the clinically approved repertoire of antiviral drugs predominantly comprises direct-acting antivirals (DAAs). However, the use of DAAs is frequently limited by adverse effects, restriction to individual virus species, or the induction of viral drug resistance. These issues will likely be resolved by the introduction of host-directed antivirals (HDAs) targeting cellular proteins crucial for viral replication. However, experiences with the development of antiviral HDAs and clinical applications are still in their infancy. With the present study, we explored the human nuclear receptor and transcription factor RORγ isoform 1 (RORγ1), a member of the retinoic acid receptor-related orphan receptor (ROR) family, as a putative target of antiviral HDAs. To this end, cell culture models were used to investigate major viral human pathogens, i.e. the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), human cytomegalovirus (HCMV), varicella zoster virus (VZV) and human immunodeficiency virus 1 (HIV-1). Our results demonstrated (i) an antiviral activity of the clinically relevant RORγ modulators cedirogant and others, (ii) that isoform RORγ1 acts as the responsible determinant and drug target in the analyzed cell culture-based models, (iii) a selectivity of the antiviral effect for RORγ1 over related receptors RORα and RORβ, (iv) a late-phase inhibition exerted by cedirogant in HCMV replication and (v) a mechanistic link to the cellular cholesterol biosynthesis. Combined, the data highlight this novel RORγ-specific antiviral targeting concept and the developmental potential of RORγ-directed small molecules.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Host-directed antiviral targeting; Major viral human pathogens; Metabolic restriction of virus replication; Novel drug targeting options; RORγ2/t modulator cedirogant; Transcriptional regulation of cholesterol biosynthesis

Viral Mimicry of Interleukin-17A by SARS-CoV-2 ORF8 - Wu, Xin; Xia, Tian; Shin, Woo-Jin; Yu, Kwang-Min; Jung, Wooram; Herrmann, Alexandra; Foo, Suan-Sin; Chen, Weiqiang; Zhang, Pengfei; Lee, Jong-Soo; Poo, Haryoung; Comhair, Suzy A. A.; et al. (Mbio, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection triggers cytokine-mediated inflammation, leading to a myriad of clinical presentations in COVID-19. The SARS-CoV-2 open reading frame 8 (ORF8) is a secreted and rapidly evolving glycoprotein. Patients infected with SARS-CoV-2 variants with ORF8 deleted are associated with mild disease outcomes, but the molecular mechanism behind this is unknown. Here, we report that SARS-CoV-2 ORF8 is a viral cytokine that is similar to but distinct from interleukin 17A (IL-17A) as it induces stronger and broader human IL-17 receptor (hIL-17R) signaling than IL-17A. ORF8 primarily targeted blood monocytes and induced the heterodimerization of hIL-17RA and hIL- 17RC, triggering a robust inflammatory response. Transcriptome analysis revealed that besides its activation of the hIL-17R pathway, ORF8 upregulated gene expression for fibrosis signaling and coagulation dysregulation. A naturally occurring ORF8 L84S variant that was highly associated with mild COVID-19 showed reduced hIL- 17RA binding and attenuated inflammatory responses. This study reveals how SARSCoV- 2 ORF8 by a viral mimicry of the IL-17 cytokine contributes to COVID-19 severe inflammation.
CRIS-Team Scopus Importer:2022-05-13
Keywords: COVID-19; inflammation; viral IL-17